DESAIN JEMBATAN T-GIRDER PADA SUNGAI JALAN ANTARA MENGGUNAKAN SNI 1725 2016 - ardy Muhamad R (LPPM Universitas Merdeka Madiun, 2020)
Bridges are part of the national transportation system that has an important facility. In Putri Sembilan Village, Rupat Utara District, there is a very important bridge where this bridge is the only alternative for residents of Putri Sembilan Village to the fishing port and plantation. The current condition of the bridge has been damaged with wood material that has been decayed and hollow. For this reason, a new bridge was planned using reinforced concrete structures. This plan refers to SNI 1725-2016 concerning the loading of bridges and SNI T-12-2004 concerning the planning of concrete structures for bridges in the hope of obtaining a bridge structure that is safe and in accordance with applicable standards. The design consists of bridge slabs, sidewalks, stamped plates, girder beams and diaphragm beams. As the result, the main reinforcement slab D16-200 mm and D13-300 mm are obtained. Reinforcement direction extending the stamp plate obtained reinforcement D16-200 mm while for the transverse obtained D16-250 mm. For the main reinforcement girder beam obtained 28D32 mm, compressive reinforcement used 8D32 mm reinforcement and shear reinforcement used Ã˜13-100 mm reinforcement. While the main reinforcement of the diaphragm beam using 3D16 mm and shear reinforcement obtained Ã˜13-200 mm reinforcement.